Microbiological profile evidenced in hemodialysis patients: A integrative literature review (Research, Society and Development, 2023)
Patients with kidney diseases can become immunocompromised, thus they are subject to several pathologies. In this sense, infection by microorganisms deserves attention, as they aggravate clinical cases, increase the time and cost of treatment, as well as increase morbidity and mortality. In this work, the objective is to determine the microbiological profile and the most frequent risk factors in hemodialysis patients in Brazil. For this, a integrative review, the articles were selected from the SciElo, BVS and LILACS databases, using the descriptors available in DeCS/MeSH: microorganism, microbiological profile and hemodialysis, which were crossed with the Boolean operator AND. Crossings were used hemodialysis AND microorganism; hemodialysis AND microbiological profile. Initially, a sample of 19 articles was obtained, but only 9 were included in the research. The important data that the main microorganisms that affect hemodialysis patients in Brazil were Gram-positive and Gram-negative bacteria, viruses (HCV and HBV) and fungi of the Candida genus. In addition, the risk factors most related to microorganisms were duration of catheterization, low income, treatment time, among others. Therefore, it is necessary to invest in the awareness of patients and professionals to prevent infections by these pathogens during hemodialysis therapy.